The impact of environmental disclosure and the quality of financial disclosure and IT adoption on firm performance: Does corporate governance ensure sustainability? - Lin, Jing; Qamruzzaman, Md (Frontiers in Environmental Science, 2023)
The study's motivation is to investigate the role of environmental and financial disclosure, IT adoption, and good governance on firms' sustainability from 1990-2019. The study considered a sample of 75 financial institutions enlisted in Bangladesh's capital market, and data were extracted from a publically annual report. Several econometrical techniques have explored the nexus between dependent and explanatory variables. Baseline assessment revealed a positive and statistically significant association between a firm's sustainability and target explanatory variables. The study extended the empirical evaluation by implementing a system-GMM and documented a positive linkage between financial and environmental disclosure, IT adaptation, good governance and the firm's sustainability. On the mediating effect of corporate governance, the study established mediating role with positive influences on financial performance augmentation. . On the policy ground, the study postulated that financial policymakers should address the fairness and integrity in disclosing the information to the public and the enforcement has to be initiated to ensure good governance.